A simple system for measuring the level of free fatty acids in human milk collected as dried milk spot. (July 2020) - Gao, Chang; Liu, Ge; McPhee, Andrew J.; Miller, Jaqueline; Gibson, Robert A.
Highlights: A dried milk spot (DMS) system for stabilising milk fats against breakdown due to endogenous lipases using microwave and analysing milk free fatty acid concentration using gas chromatography is described. The DMS method was validated against thin layer chromatography over a range of free fatty acid concentrations. We confirm that changes to the lipid classes of breast milk is independent of its total fatty acid composition. Abstract: Breast milk dried on filter paper is a useful collection device for the study of breast milk because it avoids the costs associated with cold-chain storage and transportation. Although the fatty acid profile of breast milks as dried spots is stable, changes to the composition of lipid classes of breast milk due to lipase activity have been reported and are best reflected by its free fatty acid (FFA) concentration. This study aimed to develop a robust dried milk spot (DMS) system where fats in the breast milk are stable at room temperature, and the FFA concentration of the milk can be accurately measured without interference by the high level of triglyceride, which normally constitutes around 98% of the fats in fresh milk. Our system involves applying a small amount breast milk (20 µL) on silica gel impregnated filter paper and microwaving at high power to denature lipases. At the time of analysis, the milk fats are eluted with acetone, re-constituted in heptane and injected directly into a gas chromatograph equipped with an acid modified polyethylene glycol column. This DMS method was validated against the conventional TLC method across a range of FFA concentrations. The breast milk fats collected using this DMS system are stable at room temperature for at least eight weeks which allows for transportation by post and has the potential for use in multi-centred international clinical trials.